2018
DOI: 10.1111/odi.12876
|View full text |Cite|
|
Sign up to set email alerts
|

Possible association of oestrogen and Cryba4 with masticatory muscle tendon‐aponeurosis hyperplasia

Abstract: Oestrogen and Cryba4 may be associated with the progression of masticatory muscle tendon-aponeurosis hyperplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Our previous study using proteome analysis revealed that beta-crystallin A4, which is increased by tensile force in tenocytes, is up-regulated in patients with MMTAH when compared to patients with facial deformity (FD) (4). Moreover, we showed that tendons in patients with MMTAH abundantly express decorin protein, which was induced by cyclic stretch via yes-associated protein signaling (5). The progression of this disease advances slowly from adolescence.…”
mentioning
confidence: 93%
“…Our previous study using proteome analysis revealed that beta-crystallin A4, which is increased by tensile force in tenocytes, is up-regulated in patients with MMTAH when compared to patients with facial deformity (FD) (4). Moreover, we showed that tendons in patients with MMTAH abundantly express decorin protein, which was induced by cyclic stretch via yes-associated protein signaling (5). The progression of this disease advances slowly from adolescence.…”
mentioning
confidence: 93%
“…A physiological dose of estrogen increased the levels of scleraxis and tenomodulin (markers of tendon development) in TT-D6 tenocytes. A mechanical loading assay using tensile force revealed that tensile force increases the Cryba4 levels in tenocytes21. This suggests that mechanical stress may affect tendon differentiation.…”
Section: Etiologymentioning
confidence: 96%
“…Proteomics analysis showed that the pattern of fibrinogen fragment-D, and crystallin CRYBA4 was characteristic in the temporal tendon of patients with MMTAH [ 17 ]. To elucidate the environmental factors of this disease, Hayashi et al [ 18 , 19 ] examined the effect of cyclic stretch on tenocytes and found that the expression of CRYBA4 mRNA was increased and the abundance of the decorin protein was increased via the yes-associated protein. Recently, Ito et al [ 20 ] showed that the response to mechanical stretching stress was different in the temporal tendon and the Achilles tendon.…”
Section: Introductionmentioning
confidence: 99%
“…Acquired factors, such as gliding and clenching, can have the same effect on the masticatory tendons. Indeed, Sato, Yoda, and coworkers [ 17 , 18 , 19 ] demonstrated that the pathogenesis of MMTAH was dependent on environmental factors and that the cyclic strain differentially affected the gene expression in the Achilles tendon and tendons of the masticatory muscles [ 20 ]. Moreover, hyperplasia always develops bilaterally, and MMTAH is more common in women than in men [ 8 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation